Bite-angle bending as a key for understanding group-10 metal reactivity of d10-[M(NHC)2] complexes with sterically modest NHC ligands12. Issue 2 (12th December 2014) - Hering, Florian; Nitsch, Jörn; Paul, Ursula; Steffen, Andreas; Bickelhaupt, F. Matthias; Radius, Udo
Abstract : Experimental and theoretical investigations on the novel 14 VE complexes [M 0 (iPr2 Im)2 ] (M = Pd3, Pt4 ; iPr2 Im = 1, 3-di-isopropyl-imidazolin-2-ylidene) and a comparison to their Ni congener reveal that NHC–M–NHC angle bending is a key to understand the reactivity of d 10 -[M(NHC)2 ] complexes. Abstract : Synthesis, characterization and investigations on the reactivity of the novel metal basic, yet isolable 14 VE NHC-complexes [M 0 (iPr2 Im)2 ] (M = Pd3, Pt4 ; iPr2 Im = 1, 3-di-isopropyl-imidazolin-2-ylidene; VE = valence electron; NHC = N-heterocyclic carbene) is reported and compared to the chemistry of the corresponding nickel complex. Quantum chemical analyses reveal that differences in the reactivity of group 10 NHC complexes are caused by differences in the rigidity and thus activation strain associated with bending the corresponding d 10 -[M(NHC)2 ] fragments during reaction. These results should have implications for the understanding of the fundamental steps in catalytic cycles, in which such complex fragments are employed.